Comparative Performance of Honey Production from Two Different Bee Hives in Bangladesh (The Agriculturists, 2019)
The study was conducted in three districts viz., Sirajgonj, Gazipur and Satkhira during the mustard, litchi, and mangrove blooming period, respectively during 2015-2016 and 2016-2017 cropping seasons to study honey production efficiency of traditional hive and poly super hive. The study was carried out in paired plot design. Fourteen boxes were used in each setup, among them seven were traditional hive and seven were poly super hive. In Ullapara of Sirajganj district during 2015-16 poly super hive yielded the highest (17.03 kg hive-1season-1) honey. In 2016-17 (mustard) the highest honey was harvested from poly super hive operated at Tarash (18.63 kg hive-1season-1) and the lowest honey yielded in poly super hive at Shahjadpur. At Kapasia of Gazipur during 2015-2016 (litchi) the poly super hive produced the highest (20.46 kg hive-1season-1) honey yield cropping season and the lowest (20 kg hive-1season-1) was in Kaliganj (Gazipur district). On the other hand, during 2016-2017 it was observed that in poly super hive produced the highest (14.92 kg hive-1season-1) honey operated in Gazipur Sadar and the lowest (13.93 kg hive-1season-1) was in Kaliganj. In Satkhira during 2015-16 cropping season (mangrove) the poly super hive gave the highest (14.92 kg hive-1season-1) honey yield and it was obtained from Tala and the lowest (14.65 kg hive-1season-1) honey was yielded and it obtained in Kaliganj. Again during cropping season 2016-17 poly super hive produced the highest (12.5 kg hive-1season-1) honey and it was from Tala and the lowest (11.45 kg hive-1season-1) in Munshiganj. There was significantly less honey production was recorded in traditional bee hives than the poly super hive. During 2016-17 season honey production was higher than 2015-16 season at Sirajganj. However, opposite result was observed at Gazipur and Satkhira.The Agriculturists 2019; 17(1-2) 102-111